Quantitative sensory testing in elderly: longitudinal study - Luciana Alvarenga da Silva; Omar Jaluul; Manoel Jacobsen Teixeira; José Tadeu Tesseroli de Siqueira; Wilson Jacob Filho; Silvia Regina Dowgan Tesseroli de Siqueira (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: To evaluate elderly patients in a geriatric service, along with their sensory characteristics and their association with clinical aspects. Methods: This was a descriptive longitudinal study. We enrolled 36 healthy participants of both sexes in this study. The following instruments were used and evaluations performed: clinical evaluation, Mini-Mental State Exam, and quantitative sensory testing. Results: During the follow-up, there was reduction of mean corpuscular volume at each evaluation (p < 0.001) and significant increase in mean corpuscular hemoglobin concentration (p < 0.001). There was an increase of the olfactory (p < 0.001), salty (p = 0.024), sour (p = 0.020), bitter (p = 0.001), facial cold (p = 0.019), hand cold (p = 0.004), facial tactile (p < 0.001), hand tactile (p = 0.012) and facial vibration (p = 0.018) thresholds. Previous existing morbidities were associated with sensitivity changes in the individuals in this sample. Conclusion: This longitudinal study suggests that the loss of sensitivity with aging may be associated with the presence of morbidities in elders.